Improving Teacher Competence in Managing Information Technology-Based Learning Materials - Sagiman, Sagiman; Putra, Muksal Mina (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2023)
Teacher Competency Standards are measures that determine the competence and professionalism of teachers. Hence, competence in managing learning materials is essential for the learning process. In the era of the Fourth Industrial Revolution (4.0), educators are expected to be proficient in managing information technology-based learning materials, ensuring that the content delivered to students is of higher quality, ultimately leading to expected learning outcomes. This community service program aimed to improve teacher competence in managing information technology-based learning materials through Information and Communication Technology (ICT) training. The contents included basic knowledge regarding ICT, learning material management applications, graphic design, practical training in managing learning materials, internet, and internet-based learning (e-learning). The method employed in the present community service was Participatory Action Research (PAR). The project involved 25 school teachers, resulting in an improvement in teacher competence in managing information technology-based learning materials and fostering strong motivation among teachers to utilize information technology media for gathering materials and implementing the learning process.